The shifting regulation and competition interface - Max Huffman (Market and Competition Law Review)
Antitrust and market regulation, rather than being “flip sides of the same coin,” populate a spectrum that ranges from a truly laissez faire economic system at one end to a command economy at the other. Competition policy and regulation have different strengths and will thus be preferred in different settings, as well as at differ- ent times in the chronology of industry growth. While competition policy might be favoured early in the growth of an industry, when the efficient outcomes are unknown and unknowable, regulation is a preferred approach when the industry is mature, inno- vation has slowed, and gains come from operational efficiencies rather than techno- logical changes. Their different strengths may also emerge independent of chronology: competition policy is a preferred market oversight mechanism when efficient outcomes are consistent with larger social, political, environmental – etc. – goals. Where efficient outcomes deviate from those, however, market regulation is the better alternative. The reality of the regulation-competition interface belies the binary of these as alter- native approaches to market oversight. Competition policy may be more or less regu- latory in nature and enforcers take on regulation-like approaches when their goals diverge from competitive equilibria. Competitive equilibria in labour markets are unlikely to produce worker protec- tions that serve broader social goals. This is because labour markets reflect durable monopsony power, with workers locked into employment relationships and unable to bargain effectively. The resulting equilibrium will see firms that are both employ- ers and producers favouring efficiencies in consumer markets, where they are more likely to encounter competition, over labour markets, to the detriment of workers. Competition policy gives way to regulation as prohibitions on no-compete covenants and exemptions for labour organization intrude on marketplace competition1. In a market of gig economy platforms, characterized by diffuse buyers, diffuse sellers, and a consolidated intermediary – the platform – which is protected by entry barriers including network effects and capital intensiveness, the competitive equilibrium will see surplus wealth gained by the platform. This outcome does not prevent substantial social benefits, including those realized by workers and consumers on the platform. For example, evidence suggests that the US-based gig platform Uber brought eco- nomic opportunity to developing world locations as underemployed workers became independent businesspersons and consumers had cheaper and safer means of trans- port. Regulating to protect consumers (safety regulation) and workers (minimum earnings regulation) can protect non-competition social goals including safety and equity of wealth distribution2. The market for artificial intelligence technologies is nascent, fast developing, and far from fully understood. This is also a market in which innovation is crucial, and comprehensive regulation would undermine the experimental process by which tech- nologies are developed. But the unrestricted growth of this market presents risks that demand interventions. Regulation can establish parameters within which competition might flourish, through forbidding edge-case applications, encouraging standardiza- tion of technologies, and monitoring markets to identify enduring inequities early. Regulation and competition policy populate a spectrum of market oversight options, at the extremes operating individually and, in the heartland, playing a complemen- tary role. As policymakers and enforcers continue to emphasize goals that competitive equilibria cannot achieve, regulation will play an increasingly important role.